The Development of Learning Material of Reading Complex Prosedure Text with CLIL Aproach for Vocational High School Students (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The objectives of this research are: (1) to describe the need of developing learning materials to read the text of complex procedures with CLIL approach for students of SMK based on students 'and teachers' perceptions; (2) Formulate principles of development of learning materials read text of complex procedures with CLIL approach for vocational students, (3) Develop prototypes of instructional materials read text of complex procedures with CLIL approach for vocational students, (4) descriptive test results of prototypes of learning materials reading text of complex procedures with CLIL approach for vocational students, (5) Measuring the effectiveness of learning materials reading complex text procedures CLIL approach for vocational students. The design of this research is the R & D approach (Reseach and Development) with the research step that is (1) preliminary survey, (2) planning, (3) product design, (4) product validation, (5) revision and improvement, (6) limited trial, (7) research.